Inequality at the Starting Line: Underrepresentation in Gifted Identification and Disparities in Early Achievement - Daniel A. Long; D. Betsy McCoach; Del Siegle; Carolyn M. Callahan; E. Jean Gubbins (SAGE Publishing, 2023)
Is underrepresentation of Black students, Latinx students, English learners (EL), and students from economically challenging communities in gifted programs due to inequality in early academic achievement or bias in the gifted identification process? Using three-level multilevel logistic models, we examine the degree to which the disparities in gifted identification are due to disparities in early achievement. Our datasets include 3rd-, 4th-, and 5th-grade achievement scores and demographic variables from all students in a 3rd-grade, 2011-2012 cohort across three states. Students who qualified for free/reduced-price lunch (FRPL), EL, and Black or Latinx students were between two to eight times less likely to be identified as gifted compared to non-free/reduced-price lunch, non-EL, and White or Asian students. However, between 50% and 100% of gifted identification disparities could be explained by student-level differences in early academic achievement, which is consistent with an opportunity gap explanation of underrepresentation.